Upper Limb Stroke Rehabilitation Using Surface Electromyography: A Systematic Review and Meta-Analysis - Munoz-Novoa, Maria; Kristoffersen, Morten B.; Sunnerhagen, Katharina S.; Naber, Autumn; Alt Murphy, Margit; Ortiz-Catalan, Max (Frontiers in Human Neuroscience, 2022)
Background:Upper limb impairment is common after stroke, and many will not regain full upper limb function. Different technologies based on surface electromyography (sEMG) have been used in stroke rehabilitation, but there is no collated evidence on the different sEMG-driven interventions and their effect on upper limb function in people with stroke.Aim:Synthesize existing evidence and perform a meta-analysis on the effect of different types of sEMG-driven interventions on upper limb function in people with stroke.Methods: PubMed, SCOPUS, and PEDro databases were systematically searched for eligible randomized clinical trials that utilize sEMG-driven interventions to improve upper limb function assessed by Fugl-Meyer Assessment (FMA-UE) in stroke. The PEDro scale was used to evaluate the methodological quality and the risk of bias of the included studies. In addition, a meta-analysis utilizing a random effect model was performed for studies comparing sEMG interventions to none-sEMG interventions and for studies comparing different sEMG interventions protocols.Results: Twenty-four studies comprising 808 participants were included in this review. The methodological quality was good to fair. The meta-analysis showed no differences in the total effect, assessed by total FMA-UE score, comparing sEMG interventions to none-sEMG interventions (14 studies, 509 participants, SMD 0.14, P 0.37, 95% CI −0.18 to 0.46, I² = 55%). Similarly, no difference in the overall effect was found for the meta-analysis comparing different types of sEMG interventions (7 studies, 213 participants, SMD 0.42, P 0.23, 95% CI −0.34 to 1.18, I² = 73%). Twenty out of the twenty-four studies, including participants with varying impairment levels at all stages of stroke recovery, reported statistically significant improvements in upper limb function at post-sEMG intervention compared to baseline.Conclusion:This review and meta-analysis could not discern the effect of sEMG in comparison to a none-sEMG intervention or the most effective type of sEMG intervention for improving upper limb function in stroke populations. Current evidence suggests that sEMG is a promising tool to further improve functional recovery, but randomized clinical trials with larger sample sizes are needed to verify whether the effect on upper extremity function of a specific sEMG intervention is superior compared to other none-sEMG or other type of sEMG interventions.